(untitled) (International conference on multidisciplinary science, 2024)
The advent of cloud computing has revolutionized various sectors, including library services. This thesis explores the impact of cloud computing technologies on the efficiency, accessibility, and overall service quality of libraries. By leveraging cloud-based solutions, libraries can offer enhanced digital services, streamline operations, and improve user experiences. This research delves into the benefits, challenges, and future prospects of integrating cloud computing into library services.